PENCEMARAN PESTISIDA DALAM BUDIDAYA PERTANIAN DAN UPAYA PENGENDALIANNYA - Daru Mulyono (Jurnal Rekayasa Lingkungan)
The using of pesticides for agricultural pest control usually directed to plants, whereas almost of them are fall into soil. In the soil, the pesticides are very dinamics in concentration, because of several processes occur, such as chemical, and microbial processes. There are a tend that the pesticide have bad impact within the soil for crops production, especially the pesticides which have persistent active ingredient. For this reason, therefore are needed some particular soil managementin order to reduce or overcome the bad impact of pesticides in the soil. The some particular soil management are: soil tillage, using of organic matter, limming, irrigation, and application of microbial technique.Key words : pesticide, pollution